Pengaruh Terapi Pijat Bayi Terhadap Kenaikan Berat Badan pada Bayi Usia 6-12 Bulan - Widayati; Yusfani Oktafiana (Prosiding Seminar Nasional dan CFP Kebidanan Universitas Ngudi Waluyo, 2022)
Infancy is a golden period in the development of a person who is very sensitive to his environment and the process of growth and development. One of the causes of the baby's weight problem is decreased appetite, this can be overcome by providing massage touch stimulation which can increase vagus nerve tone activity, levels of gastrin and insulin absorption enzymes so that food absorption is better and gastric emptying is faster so that it stimulates appetite baby. The purpose of this study was to determine the effect of infant massage therapy on weight gain in infants aged 6-12 months in the working area of the Margorejo Pati Health Center. Using quantitative research pre-experimental one group-test pre-post test design. The population of all infants aged 6-12 months who came for weighing in December in the working area of the Margorejo Health Center was 194 babies. Samples were taken 15 infants were selected according to the inclusion criteria, using a purposive sampling technique. The independent variable is baby massage and the dependent variable is the increase in the baby's weight. Using SOP instruments and scales. The analysis used univariate and bivariate analysis with paried t-test statistik statistic The average pretest is 7.34 kg, the lowest weight is 6 kg and the highest weight is 9.40 kg. The average posttest is 7.72 kg, the lowest weight is 6.10 kg and the highest weight is 9.60 kg. The results of the paried T-test statistic with an error rate of : 0.05 showed a significant value of p (value) 0.01 < (0.05), so H1 was accepted. There is an Influence of Infant Massage Therapy on the Weight Gain of Infants Age 6 – 12 Months in the Working Area of the Margorejo Pati Health Center. AbstrakMasa bayi merupakan golden period dalam perkembangan seseorang yang sangat peka terhadap lingkungannya dan proses tumbuh kembang. Salah satu penyebab permasalahan berat badan bayi adalah nafsu makan menurun, hal tersebut dapat diatasi dengan memberikan stimulasi sentuhan pijatan yang dapat meningkatan aktivitas tonus nervus vagus, kadar enzim penyerapan gastrin dan insuli sehingga penyerapan makanan menjadi lebih baik dan pengosongan lambung lebih cepat sehingga merangsang nafsu makan bayi. Tujuan penelitian ini mengetahui Pengaruh Terapi Pijat Bayi Terhadap Kenaikan Berat Badan Bayi Usia 6-12 Bulan Di Wilayah Kerja Puskesmas Margorejo Pati. Menggunakan penelitian kuantitatif pra-ekprerimental one group-test pra-post test design. Populasi seluruh bayi usia 6-12 bulan yang datang penimbangan bulan desember di wilayah kerja puskesmas margorejo sebanyak 194 bayi. Sampel diambil 15 bayi dipilih sesuai kriteria inklusi, menggunakan teknik purposive sampling. Variabel independen pijat bayi dan variabel dependen kenaikan BB bayi. Menggunakan instrumen SOP dan timbangan. Analisis yang digunakan analisis univarit dan bivariat dengan statistik uji paried t-test. Rata-rata pretest 7.34 kg, BB terendah 6 kg dan BB tertinggi 9.40 kg. Rata-rata posttest 7.72 kg, BB terendah 6.10 kg dan BB tertinggi 9.60 kg. Hasil uji statistik paried T-test tingkat kesalahan α : 0,05 menunjukan nilai signifikan p (value) 0.01 < α (0.05), sehingga H1 diterimaTerdapat Pengaruh Terapi Pijat Bayi Terhadap Kenaikan BB Bayi Usia 6 – 12 Bulan Di Wilayah Kerja Puskesmas Margorejo Pati.